Stop Bullying, Start Caring: Edukasi Untuk Siswa SDN X Padang Galanggang - Lisa Arista; Neci Mukherji; Zahratul Khairiyah; Bagas Fajriansyah; Hilma Asra (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2025)
Bullying, or aggressive behavior that is carried out repeatedly to dominate, hurt or make the victim feel afraid, is a serious issue in social dynamics. The type of research in this article is qualitative research using literature review and case study methods. During the delivery or prevention of bullying carried out on elementary school students at SDN X Padang Gelanggang using observation and focus group discussion methods, the students seemed to understand what bullying is. During the delivery of material regarding bullying aimed at elementary school children, the children initially did not really know what bullying is, but after being given the material, the children seem to understand what bullying is and can give examples of how to prevent bullying from happening.